2008
DOI: 10.5433/1679-0359.2008v29n2p277
|View full text |Cite
|
Sign up to set email alerts
|

Influência do diâmetro de estacas no enraizamento de Tecoma stans (L.) Juss. ex Kunth

Abstract: ResumoTecoma stans (L.) Juss. ex Kunth (Bignoniaceae), árvore nativa das Américas e Antilhas, foi introduzida no Brasil para fins ornamentais e tornou-se uma espécie invasora de áreas degradadas e pastagens na região sul. No Estado do Paraná é considerada uma planta invasora nociva, proibida a sua entrada, o plantio, o transporte, a produção e o comércio de mudas, sementes, pedaços de caules e raízes. O trabalho teve como objetivo comprovar o potencial de enraizamento de estacas caulinares lenhosas de Tecoma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
2
2
0
4
Order By: Relevance
“…P. peroba can propagate vegetatively by the mini-cutting technique, with satisfactory porcentages of survival and rooting, and crucial variables, and considered as the most important in the study of mini-cutting technique. The S (%) and R (%) of the P. peroba mini-cuttings were similar to other species of the family Bignoniaceae such as Handroanthus heptaphyllus (Freitas et al, 2016) and Tecoma stans (Biondi et al, 2008), which showed greater than 80% survival and 50% rooting of mini-cuttings. The hypothesis that the substrate influences on the rooting of the P. peroba mini-cuttings was also confirmed.…”
Section: Substrates and Iba In Rhizogenesis Of Paratecoma Perobasupporting
confidence: 53%
“…P. peroba can propagate vegetatively by the mini-cutting technique, with satisfactory porcentages of survival and rooting, and crucial variables, and considered as the most important in the study of mini-cutting technique. The S (%) and R (%) of the P. peroba mini-cuttings were similar to other species of the family Bignoniaceae such as Handroanthus heptaphyllus (Freitas et al, 2016) and Tecoma stans (Biondi et al, 2008), which showed greater than 80% survival and 50% rooting of mini-cuttings. The hypothesis that the substrate influences on the rooting of the P. peroba mini-cuttings was also confirmed.…”
Section: Substrates and Iba In Rhizogenesis Of Paratecoma Perobasupporting
confidence: 53%
“…Arg. Biondi et al (2008) avaliaram diferentes diâmetros de estacas (T1 = 0,60 a 0,80 cm; T2 = 0,81 a 1,00 cm e T3 = 1,01a 1,20 cm) no enraizamento de ipê-de-jardim, Tecoma stans, após 100 dias e verificaram ausência de efeito, porém todos os tratamentos tiveram 100% de estacas enraizadas. Os resultados obtidos no presente estudo não estão de acordo com o autor citado, atribuindo-se a diferença de resultados às características intrínsecas das espécies.…”
Section: Resultsunclassified
“…Os maiores comprimentos das brotações em função do aumento do diâmetro das estacas estão de acordo com Biondi et al (2008), que verificaram efeito significativo dos diâmetros de estacas de ipê-de-jardim, Tecoma stans sobre o comprimento das brotações, onde observaram maior comprimento de brotos nas estacas com diâmetro de 1,01-1,20 cm e menor nas estacas com 0,60-0,80 cm. Os resultados podem ser atribuídos não somente à maior reserva das estacas, mas também ao maior número de raízes observado nas estacas com diâmetro D3, consequentemente, as mesmas tiveram suprimento hídrico e nutricional maior que as demais estacas com diâmetro D1 e D2, o que proporcionou maior crescimento das brotações.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…This species produces a large number of seeds, which are quickly doi: 10.1590/S0100-83582016340400016 dispersed (Bredow, 2007) and exhibits easy vegetative propagation (Biondi et al, 2008). Furthermore, trumpet-flower species are difficult to control because they produce fastgrowing and vigorous sprouts after cutting, which makes mechanical control ineffective (Passini and Kranz, 1997).…”
Section: Introductionmentioning
confidence: 99%